2014
DOI: 10.1097/igc.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Lymphadenectomy in High-Risk Histologic Types of Endometrial Cancer: A Matched-Pair Study

Abstract: Lymphadenectomy in high-risk histotypes of EC does not increase perioperative morbidity or global cost and has not benefit on survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
3
13
0
3
Order By: Relevance
“…There were no significant differences between the 2 analyzed groups with respect to the surgical treatment, hospitalization related costs or global costs. These results concur with studies in high-risk EC [10] but not in low-risk EC [28]. Other authors, however, suggested that a selective LND strategy based on a preoperative prediction model is shown to be more costeffective than routine LND for EC [17].…”
Section: Disccussionsupporting
confidence: 76%
“…There were no significant differences between the 2 analyzed groups with respect to the surgical treatment, hospitalization related costs or global costs. These results concur with studies in high-risk EC [10] but not in low-risk EC [28]. Other authors, however, suggested that a selective LND strategy based on a preoperative prediction model is shown to be more costeffective than routine LND for EC [17].…”
Section: Disccussionsupporting
confidence: 76%
“…Les comorbidités connues, associées à ce cancer, majorent les risques de morbidités périopératoires. Une récente étude ne montre pas d'impact sur la survie en cas de réalisation des curages dans le cas des cancers endométriaux à haut risque [28].…”
Section: Discussionunclassified
“…Obie publikacje przez kilka lat wzbudzały kontrowersje; stawiano im zarzuty, że nie zawierają odpowiedniej reprezentacji przypadków z grupy wysokiego ryzyka oraz że liczba usuwanych węzłów była zbyt mała. Wszelkie wątpliwości rozwiało badanie typu matched-pair study z 2014 roku (7) , które objęto przypadki raka błony śluzowej trzonu macicy należące wyłącznie do grupy wysokiego ryzyka. Okazało się, że nawet w tej populacji pacjentek usuwanie węzłów chłonnych nie korelowało z czasem przeżycia.…”
Section: Rola Limfadenektomii W Raku Endometriumunclassified
“…Można odstąpić od usuwania jajników u kobiet przed 45. rokiem życia, u których rozpoznano adenocarcinoma the lack of appropriate representation of high risk cases and an insufficient number of resected lymph nodes. However, all doubts were dispelled by a 2014 matched-pair study (7) , which included only high risk cases of endometrial cancer. It was found that lymphadenectomy did not correlate with survival even in this patient population.…”
Section: Protokół Podstawowymentioning
confidence: 99%